2016
DOI: 10.1021/acs.jpclett.5b02908
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Carrier Dynamics on Material Surfaces in Space and Time using Scanning Ultrafast Electron Microscopy

Abstract: Selectively capturing the ultrafast dynamics of charge carriers on materials surfaces and at interfaces is crucial to the design of solar cells and optoelectronic devices. Despite extensive research efforts over the past few decades, information and understanding about surface-dynamical processes, including carrier trapping and recombination remains extremely limited. A key challenge is to selectively map such dynamic processes, a capability that is hitherto impractical by time-resolved laser techniques, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 64 publications
2
59
0
Order By: Relevance
“…The surface sensitivity can be further enhanced by reducing the accelerating voltage of the electron beam [47]. This high surface sensitivity enabled, for example, the study of surface states and surface morphology and their effects in photocarrier recombination in indium gallium nitride (InGaN) nanowires [31,49], multinary copper indium gallium selenide (CIGSe) nanocrystals [32] and CdSe [50]. When used in the environmental SEM mode, SUEM can also study photocarrier dynamics on sample surfaces in the presence of water vapor and other gases [29].…”
Section: Recent Resultsmentioning
confidence: 99%
“…The surface sensitivity can be further enhanced by reducing the accelerating voltage of the electron beam [47]. This high surface sensitivity enabled, for example, the study of surface states and surface morphology and their effects in photocarrier recombination in indium gallium nitride (InGaN) nanowires [31,49], multinary copper indium gallium selenide (CIGSe) nanocrystals [32] and CdSe [50]. When used in the environmental SEM mode, SUEM can also study photocarrier dynamics on sample surfaces in the presence of water vapor and other gases [29].…”
Section: Recent Resultsmentioning
confidence: 99%
“…The nanometer escape depth of the SE probe [19,20] gives the potential to address dynamics at surfaces and interfaces of today's nano-scale devices, where many applications rely on the interplay between semiconductors and insulators. Measurements performed with USEM have shown that SE are sensitive to the excitation of electrons in semiconductors triggered by optical pulses [21][22][23], but the technique has never been applied to insulators. In this paper we report the first USEM measurement on a thin film of alumina on silicon.…”
Section: Introductionmentioning
confidence: 99%
“…For example, pump-probe microscopy with visible light is inherently limited by diffraction, and it remains a non-routine approach in spite of recent progress3. Studies of the spatiotemporal evolution of excited carriers have recently become possible using scanning ultrafast electron microscopy (SUEM)4567, a technique that combines the spatial resolution of electron microscopy and the time resolution of ultrafast lasers.…”
mentioning
confidence: 99%